ASUHAN KEBIDANAN IBU BERSALIN DENGAN ANEMIA DAN KEK PADA NY.L DI PMB NINING MUTBAIYAH, S.ST, KEC. PAMARAYAN TAHUN 2019 - Jumiati (Journal Of Applied Health Research And Development, 2020)
Anemia is a health problem experienced by women around the world, especially in developing countries (Indonesia). The frequency of pregnant women with anemia in Indonesia is relatively high at 63.5%. According to WHO 40% of maternal deaths in developing countries are related to anemia in pregnancy. The problem of malnutrition in pregnant women is still the focus of attention, these problems include anemia and pregnant women lacking chronic energy (KEK). National Riskesdas (2018) shows the proportion of KEK risk in pregnant women is 17.3%, pregnant women with nutritional and health problems have an impact on the health and safety of mothers and infants and the quality of babies born. Able to carry out comprehensive care for midwifery cases of maternity women with anemia and KEK in Mrs. L at PMB Nining Mutbaiyah, S.ST Pamarayan in 2019 in accordance with the standardization of midwifery services. The method used in this case study is qualitative. After midwifery care for women with anemia and KEK there is an increase in hemoglobin levels and nutritional status in Ny.L. The results of the implementation of midwifery care for women with anemia and KEK in Ny.L at PMB Nining Mutbaiyah, S.ST carried out in accordance with obstetric management procedures